Monetization of sustainability indicators integrating willingness to pay into life cycle sustainability assessment - Sining, Ma; Sharaai, Amir Hamzah; Matthew, Nitanan Koshy; Zainordin, Nazatul Syadia (Human Resources Management Academic Research Society (HRMARS), 2024)
Sustainability has become a major focus of research, with life cycle sustainability assessment (LCSA) emerging as a widely used method. LCSA evaluates the three pillars of sustainability— social, environmental, and economic—through social life cycle assessment (S-LCA), life cycle assessment (LCA), and life cycle costing (LCC). However, the lack of integration among these methods, which use different units of measurement, makes it challenging for stakeholders to fully grasp the sustainability of products. To bridge this gap, monetization offers a means of translating complex environmental and social impacts into financial terms, enabling stakeholders to make more informed decisions. This review explores the monetization of LCA and S-LCA, focusing on various techniques, with the contingent valuation method (CVM) for estimating willingness to pay (WTP) identified as particularly effective. WTP allows for context-specific results that better reflect individual or organizational preferences. Future research should investigate the integration of WTP into LCSA to guide governments and stakeholders in promoting sustainable products and services.